Modeling Antarctic krill circumpolar spawning habitat quality to identify regions with potential to support high larval production - Green, DB; Bestley, S; Corney, S; Trebilco, R; Lehodey, P; Hindell, MA (Geophysical Research Letters, 2021)
Antarctic krill (krill) are important within Southern Ocean ecosystems and support an expanding fishery. Toward understanding krill's response to environmental change, it is necessary to identify regions that support high krill larval production (spawning habitat). We develop a mechanistic model combining thermal and food requirements for krill egg production, with predation pressure post-spawning, to predict regions of high-quality spawning habitat. We optimize our model regionally and generate circumpolar predictions of spawning habitat quality. Our results indicate the southwest Atlantic accounts for almost half of all predicted high-quality spawning habitat. Small-scale management units (SSMUs) around the Antarctic Peninsula had high coverage of high-quality spawning habitat. In contrast, the remaining SSMUs (except around South Georgia) were poorly covered, suggestive of population sinks reliant on input from external sources upstream. This implies strong potential for downstream impacts of fishing in key spawning areas, with implications for management of SSMUs and the krill fishery.